Exchange rate risk premium: An analysis of its determinants for the Mexican Peso-USD - Guillermo Benavides (Banco de México, 2016)
The objective of this paper is to analyze what are the main determinants of the exchange rate risk premium (ERP). The empirical case is conducted for the daily Mexican peso-USD exchange rate for a sample period from 2007 until 2015. According to the results the ERP is influenced by several financial variables which are the VIX, a carry trade index, the EMBI and the forward premium obtained from derivatives' transaction orders. These results are in line with previous results in the literature that have proven that exchange rate premiums are influenced by several financial variables, which are usually considered as "proxies" of risk.
Keywords: C22; C53; C58; G10; G13; 330; Mexican peso-USD Exchange Rate; Risk-Neutral Densities; Risk premiums